Elevated Extracellular Hsp70 Correlates with Increased IL-1 and IL-10 in Iraqi Patients with Colorectal Carcinoma: Hsp70 & IL-1/IL-10 in Iraqi CRC Patients - Ismaeel, Farah E.; Obaid, Mohamed Farhan; Al-Saffar , Ali Z.; Al-Shammari, Ahmed (Iraqi Journal of Cancer and Medical Genetics, 2023)
Colorectal cancer (CRC) is the most common cancer in the Iraqi population. Cancerous cells are stressed cells that express large amounts of intracellular and extracellular heat shock proteins to correct for distorted proteins. They also directly affect immune cells and produce large amounts of cytokines. This work aimed to study the association between serum levels of heat shock protein 70 (Hsp70), interleukin 1 (IL-1), and interleukin 10 (IL-10) in CRC patients to highlight the importance of this pathway in patients’ immune status that may affect the progression of CRC. In the current study, an enzyme-linked immune sorbent assay (ELISA) was performed in 20 Iraqi colorectal cancer patients and 20 healthy volunteers to measure serum levels of Hsp70, IL-1α, and IL-10. Serum levels of HSP70, IL-1α and IL-10 were significantly higher in the CRC group than in the healthy control group (38.83 ± 4.7 and 14.88 ± 1.74 ng mL-1), (141.4 ± 23.22 and 46.38 ± 4.4 ng mL-1) and (26.95 ± 10.14 and 1.4 ± 1.07 ng mL-1), respectively, (p < 0.0001). According to these findings of this study, Hsp70 can be used as a prognostic biomarker for CRC and may be useful in identifying patients with an increased risk of immune tolerance and CRC development in Iraqi patients.